(untitled) (Colombia Medica, 1989)
Between April 1988 and March 1989, a controlled clinical study was performed with 102 thyroid surgery patients at the ISS and HUV in Cali to evaluate the benefits of prophylactic routine drainage. Two groups were randomized (flip of a coin method): one was left with drainage, and the other was without. 102 patients with benign and malignant pathologies who underwent thyroid surgery participated. Drainage was left in 47, and 55 were left without. No significant statistical difference was seen between the two groups. Only 11 complications were seen in 10 people, 6 in the group with drainage and 4 in individuals without drainage. The complications were nine hematomas, 5 drained by reoperating the patients, and the rest drained by suction with a needle. Wound infections were seen in 2 patients, both of them belonging to the group with drainage. The authors, supported by the results obtained from this study and a literature revision, conclude that prophylactic routine drainage after thyroid surgery is unnecessary. A closed suction drain is proposed only for patients at risk for bleeding.